New records of jaguar (Panthera onca) in Península Papagayo, Guanacaste Conservation Area, Costa Rica - Araya-Gamboa, Daniela; Pomareda-García, Esther; Arroyo-Arce, Stephanny; Espinoza-Muñoz, Deiver; Araya-Jiménez, Yosette; Thomson, Ian; Chavez-Ramos, Mónica; Salom-Pérez, Roberto; Corrales-Gutiérrez, Daniel; Fonseca, Luis G. (Therya Notes, 2024)
While jaguars (Panthera onca) are known to inhabit Guanacaste Conservation Area, Costa Rica, there are sectors within the conservation area where the species has not been confirmed. Therefore, herein we document the first jaguar records in Península Papagayo, Guanacaste Conservation Area, Costa Rica. Data was collected from February to August 2022 using non-invasive methods, including camera traps and fecal DNA sampling across the study area. After 6,093 camera trap nights, we identified 2 adult jaguar individuals (male and female). Furthermore, out of 30 fecal samples collected, 4 were identified as jaguar scats. Our findings constitute the first evidence of jaguar presence in Península Papagayo, and to our knowledge, are the southernmost records along the Pacific coast of Guanacaste Conservation Area, Costa Rica.